Alginate dialdehyde (AD)-crosslinked casein films: synthesis, characterization and water absorption behavior. Issue 5 (3rd July 2016) - Bajpai, S. K.; Bajpai, M.; Shah, Farhan Ferooz
Abstract: In this work, for the first time, alginate dialdehyde (AD) has been used as a cross linker to prepare casein films. The films, synthesized, have been characterized by Fourier transform infrared spectroscopy, X-ray diffraction analysis and scanning electron microscopy and thermogravimetric analysis. The films were investigated for their water absorption capacity in the physiological fluid of pH 7.4 at 37 °C. The film samples (AD-X-CAS)12, (AD-X-CAS)24 and (AD-X-CAS)36 demonstrated an equilibrium water absorption of 30.86, 26.15 and 11.93 g/g, respectively. Moreover, the swelling exponents for the films were in the range of 0.66–0.75, thus indicating non-Fickian water transport mechanism. The dynamic water uptake data were analysed by various kinetic models. The water vapour transmission rates (WVTR) for the three film samples were found to be 16587, 15900 and 14316 g/m 2 /day, respectively. The higher values of WVTR, obtained for all the three samples, indicated their suitability for high exudating wounds. The results of expansion study in 4% gelatin medium revealed that the three samples exhibited an almost 2.54, 2.09 and 1.90-fold increase in their diameter in 90, 75 and 60 min, respectively.